Association of thyroid stimulating hormone and iron profile among patients with subclinical primary hypothyroidism - Maharjan, Suvekshya; Maharjan, Lokeshwor; Mainali, Sumnima; Lama, Anita; Gurung, Sanyukta (Journal of Physiological Society of Nepal, 2021)
Introduction: Physiologically, thyroid hormones have a vital role in maintaining metabolic balance of the human body. Subclinical hypothyroidism is often associated with hematological disorders including iron-deficiency anemia. This study aims to correlate thyroid stimulating hormone and iron profile in patients with subclinical primary hypothyroidism. Materials and methods: This is a cross-sectional study conducted in Nepal Medical College and Teaching Hospital, Kathmandu, Nepal among patients with subclinical primary hypothyroidism. The study was conducted from October 2018 to December 2019. Total of 60 patients above the age of 18 years were enrolled for the study. Thyroid function test was done by automated machine using electro chemiluminescent immunoassay technique and iron profile test was done by Immunoassay method using Vitros Analyzer. Pearson’s correlation test was applied to find the correlation between thyroid stimulating hormone and iron profile. Results: Among the 60 participants with subclinical hypothyroidism 23% were males and 77% were females with a mean age of 43 years. The mean serum iron (male =81.14 μg/dl female = 69.5 μg/dl), mean total iron binding capacity (male =470.35 μg/dl, female = 477.94 μg/ dl) and mean ferritin level (male=91.15 μg/dl, female=95.51 μg/dl) were within reference value of our laboratory. A negative correlation was observed between thyroid stimulating hormone levels and serum iron (r=0.376, P=0.003), thyroid stimulating hormone and total iron binding capacity also showed a negative correlation (r=-0.083, P=0.27). Similarly thyroid stimulating hormone and transferrin saturation also showed a negative correlation (r=-0.098, P=0.455) whereas, a positive correlation was observed between thyroid stimulating hormone and ferritin (r=0.037, P=0.779). Conclusions: This study concludes that thyroid stimulating hormone is negatively associated to serum iron, total iron binding capacity and transferrin saturation whereas, positively associated with ferritin among patients with subclinical hypothyroidism.